Waging heavy peace : a hippie dream - Young, Neil, 1945- (Blue Rider Press, 2012)
An iconic figure in the history of rock and pop culture (inducted not once but twice into the Rock and Roll Hall of Fame), Neil Young has written his eagerly awaited memoir.